Analysis of potential causes of failure in public lighting fixtures in Tierra Blanca, Veracruz, Mexico (GEON Journal (Management, Organizations and Business), 2022)
Problematic: In Tierra Blanca there are public lights with poor lighting and high recurrence in the casting of the lamps. Even though this a latent problem throughout the municipality, it’s just one side of the coin, the real problem is that there are no procedures and no skills have been shown to detect the root cause of the situation. Objectives: Determine the main causes of failure (foundry) applying quality control tools to identify and characterize potential failure in the public lighting fixtures. Materials and methods: With the methodology for the elaboration of a failure mode and effect analysis (AMEF) potential failures and their severity were determined the potential causes and their occurrences, the detection modes and their effectiveness, to finally obtain the risk priority numbers (NPR). Results: Improvement actions were proposed, which produced three different results: A format for filing complaints, determination of the four spare parts that’s should always be in storage and the three main causes of failure in public lighting lamps. Discussion: The AMEF developed must be maintained and continually improved. In this way, the improvement actions will have a methodological foundation and will allow in medium term to control the inventories of the most used spare parts, determine the times of the requirements or respect the minimum levels in existence. Conclusions: The reasons why the luminaires fail are mainly due to the melting of the spotlights and photocells, also due to the burned ballasts. Contribution / originality: Preparation of a report and complaint format that allows detailing as much information as possible about the decision reported by the citizen.
Keywords: causal analysis; cause and effect; decision making; goverment policy; lighting; problem resolution